World Literature and Translation in Persian Literature Textbooks - Nazanin Shadman; Mir Mohammad Khademnabi (Acta Universitatis Sapientiae: Philologica, 2021)
. Persian literature textbooks, designed, compiled, and distributed by a state bureau run by the Ministry of Education, Organization for Educational Research and Planning, also have sections on the theory and practice of translating world literature. The current study deals with those passages, how they are represented and how they are consequently interpreted in the light of Venuti’s conceptualization of domesticating and foreignizing translation. It is aimed to understand the status, significance, and visibility of translators in the corpus under study. The results of content analysis for the five high school literature textbooks (grades 6, 7, 8, 9, 10, 11, and 12) indicate a strong sense of domestication and appropriation by the compilers of the textbooks. The following strategies are recognized to have the largest share in the textbooks: no mention of the name of the translator, Iranization, and appropriation. The strategies are followed by samples for each theme. The paper concludes that the polyphonic world promised to be achieved by studying foreign and world literature is not, therefore, attained in such a context, as the emphasis is ultimately on the target ideologies and worldviews. The study also sheds doubt on the assumption that domestication is confined to the so-called imperialistic cultures like the Anglo-American.